An adverse social welfare effect of a doubly gainful trade - Oded Stark; Ewa Zawojska; Wilhelm Kohler; Krzysztof Szczygielski (University of Bonn, Center for Development Research (ZEF), 2018)
Acknowledging individuals' distaste for low relative income renders trade less appealing when trade is viewed as a technology that integrates economies by merging separate social spheres into one. We define a “trembling trade” as a situation in which gains from trade are overtaken by losses of relative income, with the result that global social welfare is reduced. A constructive example reveals that a “trembling trade” can arise even when trade is doubly gainful in that it increases the income of every individual and narrows the income gap between the trading populations.
Keywords: D31; D63; R12; 330; Gains from trade; Increase of incomes; Decrease of income gap; Integration; Change of social space; Low relative income; Social welfare